PENGARUH TRANSFER PRICING, UMUR PERUSAHAAN, DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK - Suciati, Sartica Eka; Sastri, Enan Trivansyah (LPPM Universitas Bina Bangsa, 2024)
This study aims to provide empirical evidence of the effect of transfer pricing, company age, and sales growth on tax avoidance. The population in this study is consumer non-cyclicals companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The type of research used is an associative quantitative approach using secondary data in the form of annual financial reports obtained from the IDX. This research uses purposive sampling. The number of samples used was 17 companies with 5 years of observation, so that the total sample of this study was 85 data. Data analysis in this study used panel data regression analysis with the help of EViews version 9 software. The results of the study simultaneously show that transfer pricing, company age, and sales growth affect tax avoidance. While the partial research results show that: (1) Transfer pricing has no effect on tax avoidance, (2) Company age affects tax avoidance, and (3) Sales growth has no effect on tax avoidance. This research is expected to provide contribution benefits in the development of theory about the effect of transfer pricing, company age, and sales growth on tax avoidance